Talented Pedagogues – Who Will Discover Them? (Training and Practice : Journal of Educational Sciences, 2015)
There are various definitions of talent as several Hungarian and foreign researchers have dealt with this topic. Different definitions represent different viewpoints and highlight different pinpoints concerning the same issue. The common thing in these definitions is that besides extraordinary performance they regard inheritance and environment as most important determinants. The concept of talent is wide and colourful, however in our national school system talents are only chosen in different school subjects. The participants of the talent support program besides the talented children are the mentors, who may be pedagogues, parents or qualified talent supporters. Talent supporters need to have an excellent sense for recognizing the potential in children, and they have to be dedicated to help the children in their developmental process. In most cases talents are supported by pedagogues, but no one deals with the issue who the talented pedagogues are, who are the ones that can fulfil this job on the highest level.